Extent of palliative care need in the acute hospital setting: A survey of two acute hospitals in the UK. (January 2013) - Gardiner, Clare; Gott, Merryn; Ingleton, Christine; Seymour, Jane; Cobb, Mark; Noble, Bill; Bennett, Mike; Ryan, Tony
Background: In common with international health policy, The End of Life Care Strategy for England has highlighted the delivery of high quality palliative care in the acute hospital setting as an area of priority. Aim: The aim of this study was to explore the extent of palliative care need in the acute hospital setting, and to explore agreement between different sources in the identification of patients with palliative care need. Design: A cross-sectional survey of palliative care need was undertaken in two UK acute hospitals. Hospital case notes were examined for evidence of palliative care need according to Gold Standards Framework (GSF) prognostic indicator criteria. Medical and nursing staff were asked to identify patients with palliative care needs. Patients (or consultees) completed assessments of palliative care need. Participants: Of a total in-patient population of 1359, complete datasets were collected for 514 patients/consultees. Results: 36.0% of patients were identified as having palliative care needs according to GSF criteria. Medical staff identified 15.5% of patients as having palliative care needs, and nursing staff 17.4% of patients. Patient self-report data indicated that 83.2% of patients meeting GSF criteria had palliative care needs. Conclusion: The results reveal that according to the GSF prognostic guide, over a third of hospital in-patients meet the criteria for palliative care need. Consensus between medical staff, nursing staff and the GSF was poor regarding the identification of patients with palliative care needs. This has significant implications for patient care, and draws into question the utility of the GSF in the hospital setting.